2014
DOI: 10.1080/20932685.2014.926129
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting the efficacy of augmented reality virtual dressing room technology as a tool for online visual merchandising

Abstract: Driven by advancements in technology and continuing improvements in the Internet, a transformation in the way consumers shop is taking place. Despite the shortcomings of remote shopping, web-based fashion sales continue to rise (Batista, 2013), and virtual dressing room (VDR) technology should contribute to this trend. Currently there are two technologies for delivering VDR online: Virtual Reality (VR) and Augmented Reality (AR). Important questions linger regarding how consumers will use these new technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 43 publications
0
60
1
3
Order By: Relevance
“…In-store virtual mirror technology is an emerging form of AR with promise to enhance in-store convenience (Perry 2016). The impact of virtual mirrors is related to the development of online virtual dressing rooms as they facilitate consumer experience of 7 virtual fitting where social interactions are present (Yaoyuneyong, Foster, & Flynn, 2014).…”
Section: Digital Fashion Consumer Behaviour Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In-store virtual mirror technology is an emerging form of AR with promise to enhance in-store convenience (Perry 2016). The impact of virtual mirrors is related to the development of online virtual dressing rooms as they facilitate consumer experience of 7 virtual fitting where social interactions are present (Yaoyuneyong, Foster, & Flynn, 2014).…”
Section: Digital Fashion Consumer Behaviour Literaturementioning
confidence: 99%
“…In the future, therefore, fit and sizing technologies should be designed to centrally enhance consumer trust in recommendation to provide an important tool for online purchasing. When considering trust, the consumers personal experience of the clothing item will heavily influence how valuable they perceive the interface and its subsequent success on product satisfaction (Yaoyuneyong et al 2014;McKinney and Shin 2016). It is evident in existing studies that consumer product reviews are an important part of interface acceptance, purchase intention and future product satisfaction.…”
Section: Fit Satisfaction Sits Between the Relationship Of Social Accmentioning
confidence: 99%
See 1 more Smart Citation
“…This forms a clear gap to be filled by the proposed research. There was a concentration of store image and store environment literature in the 1970s and 1980s which considered VM and highlighted its capacity as both a sales tool and a marketing communication device (Bitner, 1992;Donovan & Rossiter, 1982;Kotler, 1973;Mills & Paul, 1988;Yaoyuneyong, Foster, & Flynn, 2014); since then, however, there has been a lack of academic studies, which is surprising considering the growth of the VM sector and its increasing professionalism (Bailey & Baker, 2014). Lea-Greenwood (2013) notes that most fashion brands now have at least one visual merchandiser per flagship store and that display teams are now involved in key decisions with the buying and marketing departments.…”
Section: Introductionmentioning
confidence: 98%
“…Yaoyuneyong and so on have found that augmented reality (AR) affects consumers' attitudes and purchase intentions [1]. Chang and so on showed that a mobile guide system, as an aid to painting appreciation, compared with audio and non-participants, AR effectively guided tourists to enhance learning and promote their mobile experience, extend the time visitors pay attention to painting [2].…”
Section: Reviewmentioning
confidence: 99%